Keterwakilan Perempuan dalam Dewan Perwakilan Rakyat Daerah - Rodiyah, Isnaini (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
Representation of women in the political sphere can be interpreted as a form of participation in opening that the resulting policy will include the interests of all parties, whether at the local, national, and international levels. In the process of democratic issues, larger women participation, representation, and accountability are absolute prerequisites for the realization of a meaningful democracy. But in fact, in the district of Sidoarjo there is still women's lack of access making it difficult for women to show that their interests are not accommodated in the political system. This was marked by the lack (not quotas) of women representation as members of parliament in Sidoarjo. This paper is also intended to study the participation, quality, and responsibility of women's representation in the political sphere.